Influence of alloying element segregation at grain boundary on the microstructure and mechanical properties of Mg-Zn alloy - Qian, Xiaoying; Dong, Zhihua; Jiang, Bin; Lei, Bin; Yang, Huabao; He, Chao; Liu, Lintao; Wang, Cuihong; Yuan, Ming; Yang, Hong; Yang, Baoqing; Zheng, Changyong; et al. (Materials & design, 2022)
[Display omitted] •Nd promotes the co-segregation of Zn and Nd at grain boundary combination with the nanoscale (Mg, Zn)3Nd precipitates significantly refine the grain size.•Ce significantly enhances the co-segregation of Zn and Ce at the grain boundary and yields a noticeable solute drag effect on the mobility of the grain boundary.•A noticeable improvement in strength and ductility is achieved by Ce addition in Mg-Zn alloy. The role of alloying element segregation at grain boundary on the microstructure and mechanical properties is investigated in the case of Ca, Ce, and Nd addition in Mg-1Zn (wt.%) alloy. Segregation of alloying elements at grain boundary is demonstrated in all the designed ternary alloys, leading to a strong solute drag effect on the mobility of grain boundaries and ultimately the grain size. While the co-segregation of Zn and Ce is revealed in the Mg-Zn-Ce alloy, only the segregation of Zn is observed in the Mg-Zn-Ca alloy. The co-segregation of Zn and Nd in Mg-Zn-Nd alloy is demonstrated to lead to the relatively large solute drag pressure at grain boundary, which in combination with the Zener pressure emerging from nanoscale (Mg, Zn)3Nd precipitates significantly refines the grain size. The grain refinement in combination with the bimodal microstructure significantly contributes to the increased strength of the designed ternary alloys. Furthermore, the addition of Ca and Ce are found to simultaneously improve the strength and ductility, which is closely correlated with the segregation of alloying elements at the grain boundary. Among the considered alloying species, Ce is shown to efficiently improve the mechanical properties of Mg-Zn alloy.